WDHD1 Leads to Cisplatin Resistance by Promoting MAPRE2 Ubiquitination in Lung Adenocarcinoma - Gong, Lian; Xiao, Mengqing; He, Dong; Hu, Yi; Zhu, Yuxing; Xiang, Liang; Bao, Ying; Liu, Xiaoming; Zeng, Qinghai; Liu, Jianye; Zhou, Ming; Zhou, Yanhong; et al. (Frontiers in Oncology, 2020)
Ubiquitin ligases have been shown to regulate drug sensitivity. This study aimed to explore the role of the ubiquitin ligase WD repeat and HMG-box DNA binding protein 1 (WDHD1) in regulating cisplatin sensitivity in lung adenocarcinoma (LUAD). A quantitative analysis of the global proteome identified differential protein expression between LUAD A549 cells and the cisplatin-resistant strain A549/DDP. Public databases revealed the relationship between ubiquitin ligase expression and the prognosis of patients with LUAD. Quantitative real-time PCR and western blotting (WB) was used to estimate the WDHD1 expression levels. Public databases analysis predicted the substrate of WDHD1. WB detected the effect of WDHD1 on microtubule associated protein RP/EB family member 2 (MAPRE2) and DSTN. Functional analysis of MAPRE2 by MTT and flow cytometry. Immunoprecipitation, protein stability, and immunofluorescence verified the interaction between WDHD1 and MAPRE2 as well as the interacting sites. Cell and animal experiments confirmed the effect of WDHD1 and MAPRE2 on cisplatin sensitivity in LUAD. Clinical data evaluated the effect of the WDHD1 expression level on cisplatin sensitivity. Quantitative analysis of the global proteome revealed ubiquitin-dependent protein catabolism to be more active in A549/DDP cells than in A549 cells. WDHD1 expression was higher in A549/DDP cells than in A549 cells, and knocking out WDHD1 increased the sensitivity of A549/DDP cells to cisplatin. WDHD1 overexpression negatively correlated with the overall survival of LUAD patients. We observed that MAPRE2 was upregulated when WDHD1 was knocked out. A MAPRE2 knockout in A549 cells resulted in increased cell viability and decreased apoptosis when exposed to cisplatin. WDHD1 and MAPRE2 were found to interact in the nucleus, and WDHD1 promoted the ubiquitination of MAPRE2. Following cisplatin exposure, the WDHD1 and MAPRE2 knockout groups in A549/DDP cells displayed increased levels of cellular proliferation and migration, decreased apoptosis, and increased tumor size and growth rate in animal experiments. Immunohistochemistry showed that Ki67 levels increased and levels of apoptotic indicators significantly decreased in the WDHD1 and MAPRE2 knockout groups. Clinical data confirmed that WDHD1 overexpression negatively correlated with cisplatin sensitivity. Thus, the ubiquitin ligase WDHD1 induces cisplatin resistance in LUAD by promoting MAPRE2 ubiquitination.